Integrating Chinese and western medicine for COVID‐19: A living evidence‐based guideline (version 1). Issue 4 (11th October 2021) - Ge, Long; Zhu, Hongfei; Wang, Qi; Li, Mengting; Cai, Jianxiong; Chen, Yang; Chen, Yaolong; Ding, Banghan; Fang, Bangjiang; Fei, Yutong; Feng, Jihong; Guo, Xinfeng; et al.
Abstract: Background: The coronavirus disease 2019 (COVID‐19) has turned into a pandemic and resulted in huge death tolls and burdens. Integrating Chinese and western medicine has played an important role in the fight against the COVID‐19 pandemic. Purpose: We aimed to develop a living evidence‐based guideline of integrating Chinese and western medicine for COVID‐19. Study design: Living evidence‐based guideline. Methods: This living guideline was developed using internationally recognized and accepted guideline standards, dynamically monitoring the release of new clinical evidence, and quickly updating the linked living systematic review, evidence summary tables, and recommendations. Modified Delphi method was used to reach consensus for all recommendations. The certainty of the evidence, resources, and other factors were fully considered, and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach was used to rate the certainty of evidence and the strength of recommendations. Results: The first version of this living guidance focuses on patients who are mild or moderate COVID‐19. A multidisciplinary guideline development panel was established. Ten clinical questions were identified based on the status of evidence and a face‐to‐face experts' consensus. Finally, nine recommendations were reached consensus, and were formulated from systematic reviews of the benefits and harms, certainty of evidence, public accessibility, policy supports, feedback on proposed recommendations from multidisciplinary experts, and consensus meetings. Conclusion: This guideline panel made nine recommendations, which covered five traditional Chinese medicine (TCM) prescription granules/decoction (MXXFJD, QFPD, XFBD, TJQW, and JWDY), three Chinese patent medicines (LHQW granules/capsule, JHQG granules, and LHQK granules), and one Chinese herbal injection (XBJ injection). Of them, two were strongly recommended (LHQW granules/capsule and QFPD decoction), and five were weakly recommended (MXXFJD decoction, XFBD decoction, JHQG granules, TJQW granules, and JWDY decoction) for the treatment of mild and moderate COVID‐19; two were weakly recommended against (XBJ injection and LHQK granules) the treatment of mild and moderate COVID‐19. The users of this living guideline are most likely to be clinicians, patients, governments, ministries, and health administrators.